(3GdEUOGQ hGdEjQGO hGdJfHjg Ydi eSGdc GdQTGOs - (3CHh GdaVd LYaQ Hf CMeO Hf YHO GdSdGes ((3MejO Hf CMeO Hf eMeO Hf CMeO GdeMdi s)
(3ChdgG (B:s
(3GdMeO ddg hMOg hbaJ Ydi cJGH Gdabjg GdCLd GdSjO GdCaVd COGe Gddg Ydjg ShGHZ aVdg hQMeJg Yf GdEYJQGVGJ GdChdi s
(3BNQgG (B:s
(3hEPG UMJ GdYQhS WdHJ GdKeGQ efgG , hai gPg GdLedI JbhQjg dCSHGH GdhOGO hbVGA deG jdRe ef Mb GdJYgO hJfHjg Ydi eOGNd GdEUOGQ hGdEjQGO s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdJhMjO hGdedd hGdfMds